1998
DOI: 10.1136/gut.42.5.721
|View full text |Cite
|
Sign up to set email alerts
|

Liver/kidney microsomal antibody type 1 and liver cytosol antibody type 1 concentrations in type 2 autoimmune hepatitis

Abstract: Background-Liver/kidney microsomal antibody type 1 (LKM1) and liver cytosol antibody type 1 (LC1) are the serological markers of type 2 autoimmune hepatitis (AIH). Aims-Since LKM1 and LC1 react against two distinct liver specific autoantigens (cytochrome P450IID6 (CYP2D6) and a 58 kDa cytosolic polypeptide respectively), the aim was to see whether LKM1 and LC1 concentrations correlate with liver disease activity. Patients-Twenty one patients with type 2 AIH were studied.Methods-All sera were tested by indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 24 publications
(15 reference statements)
2
65
0
2
Order By: Relevance
“…Interestingly, anti-LC1 autoantibody titers were found to parallel disease activity in type 2 AIH patients. 19 These observations suggest that a loss of B cell tolerance against hepatic autoantigens could be an initial and fundamental step in the development of late-onset liver autoimmunity.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, anti-LC1 autoantibody titers were found to parallel disease activity in type 2 AIH patients. 19 These observations suggest that a loss of B cell tolerance against hepatic autoantigens could be an initial and fundamental step in the development of late-onset liver autoimmunity.…”
Section: Discussionmentioning
confidence: 96%
“…The latter is suggested by the finding that global levels of circulating LC1 seem to parallel, at least biochemically, the occurrence of liver damage in LC1-positive patients with autoimmune hepatitis. 6 It is likely that there is a relationship between the B-cell (and possibly T-cell) epitope spreading process and the exacerbations and remissions of autoimmune liver disease. FIG.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In addition, serum LC1 concentrations appear to fluctuate in parallel with aminotransferase levels, an observation that suggests a possible role of LC1 autoreactivity in the pathogenic mechanisms leading to hepatocyte injury. 6 In a recent report, Lapierre et al after screening a complementary DNA (cDNA) library of HepG2 cells with an LC1-positive serum isolated a clone with high sequence homology to pig formiminotransferase cyclodeaminase (FTCD), and showed that a construct encoding the C-terminal portion of FTCD can be recognized by LC1 antibodies. 7 FTCD is a mammalian metabolic enzyme involved in the conversion of histidine to glutamic acid, 8 and is most highly expressed in the liver.…”
mentioning
confidence: 99%
“…Anti-SLA antibodies denote patients with a more severe course of AIH and a propensity for relapse after corticosteroid withdrawal compared to their negative counterparts [49,81,121,122] . AIH-2 patients with anti-LC1 antibodies have histologically more severe disease compared to those without anti-LC1 antibodies [35,123,124] . PBC AMA titres do not seem to be associated with disease severity but those of the IgG3 subclass may identify patients prone to develop more severe disease compared to those without AMA-IgG3 [116,125] .…”
Section: Aihmentioning
confidence: 98%